Coloured education struggles in South Africa : education boycotts in the Western Cape, 1976 - Bond, David Francois de Beer (Department of Political Studies, 2023)
This is an empirical study which is inf owned by a broad theoretical perspective. A major part of the work is a historically descriptive investigation of the Coloured education system and related conflict in South Africa. The work's main focus is an analysis of the Coloured participation in an initially African education protest which developed into a national political revolt. The South African State requires an ideological force to gain the Black populace's acceptance of the government's legitimacy and, thus, to bolster its political supremacy. Education institutions are examples of mechanisms which the State can employ for such ideological and political purpose. Such institutions do not, however, have an ideological function for the State alone; education becomes a contested terrain because both rulers and ruled seek its use for their opposing political ends. This theoretical approach is reflected in the study's focus on the Coloured population category's opposition to elements of the State education system. This study displays the relationship between education, ideology, and politics. The government's attempt to propound its ideology through education is manifest in the examination of the Coloured education system. The contrasting hopes and idea is of Coloureds give rise to a series of educational struggles. The examination of these reveals distinct phases which are characterised by an altered opposition leadership, new political trends, new organisational fonts and internal ideological divisions. Much of this study traces the historical development of Coloured educational and related political protest fran 1948 to 1976. This historical analysis aims to explain the emergence, in 1976, of educational institutions as the main site of national struggle and the reasons for the Coloured role therein. Armed with the essential historical context, the study provides a detailed analysis of the Coloured participation in the 1976 events. It examines mobilisation, motives and methods; alliances, organisations and focus; conditions, conflicts and consequences. The Coloured role in the 1976 events was a continuation of educationally and politically linked struggles of the past; was significantly new due to more recent political developments, the emergence of new student and scholar organisations and the growth of the Black Consciousness ideology. The study shows that Coloured participation in the Black education struggles of 1976, despite certain limitations, posed a significant challenge to government ideological and political hegemony in South Africa.